The Difference in Antibacterial Potency of the Infusion of Akar Kuning (Fibraurea tinctoria Lour.) against Shigella dysenteria and Salmonella typhi In Vitro - Mohammad Bakhriansyah; Divae Sandrainy; Agung Biworo (Berkala Kedokteran, 2021)
Abstract: Akar kuning (Fibraurea tinctoria Lour.), an original plant from Kalimantan, is often used by the community as traditional medicine. Previous studies showed that akar kuning contains active compounds such as alkaloids, flavonoids, saponins, and terpenoids that have antibacterial properties. This study aims to analyze the difference in antibacterial potency of the infusion of akar kuning against the growth of Shigella dysenteriae (S. dysenteriae) and Salmonella typhi (S. typhi) in vitro. This was a true experimental study with a post-test method only with control group design using the infusion of akar kuning with concentrations of 16%, 32%, and 64%, 5 µg ciprofloxacin as the positive control and aquadest as the negative control. The data were analyzed using the One-Way ANOVA test, LSD’s Post-hoc test, and independent T test with a 95% of confidence level. This study showed that the higher the concentration of the infusion of akar kuning, the larger the inhibition zone of the infusion at the concentration of 64% had a larger inhibition zone for S. typhi (16,32 mm) than S. dysenteriae (15,59 mm). However, there was no statistical difference in antibacterial potency of  the infusion of akar kuning against S. dysenteriae and S. typhi.  Keywords: antibacterial potential, infusion, akar kuning, Fibraurea tinctoria Lour., Shigella dysenteriae, Salmonella typhi